PEMBERDAYAAN MASYARAKAT DESA SAWAHAN DI MASA PANDEMI COVID-19 DENGAN PELATIHAN WIRAUSAHA JAMU INSTAN - Anif Nur Artanti; Intan Muslimah; Bella Azzahra Aqira Averillia; Diyah Ayu Kumalasari; Fadillah Nur Aini; Fitria Lidini Hanifah; Fitrilia Rachma Ardana; Najla Anisah Qumairoh; Rahma Nur Fitriana; Sandra Dwi Fantika; Sukmania Indra Alvianti Ningsih (Universitas Mataram, 2022)
The Covid-19 pandemic has an impact on all levels and aspects of people's lives, including health, economy, education, and social life. The pandemic that has been going on since the end of 2019 has forced people to fight hard to maintain their survival, including people in Sawahan Village, Ngemplak District, Boyolali Regency. The public is required to adapt to the pattern of life in the era of the Covid-19 pandemic, namely a new pattern of habits regarding the discipline of the Covid-19 health protocol which aims to reduce the transmission of the Covid-19 virus outbreak. This community service activity aims to build immune-enhancing instant herbal medicine entrepreneurs based on ginger, temulawak, and turmeric. The legality of the instant herbal medicine is through the BPOM permit, which is in the process of permitting and production in collaboration with industrial partner CV PJ ChingLung. Community service activities are carried out in several stages, namely program socialization to the community and training on making instant herbal medicine which is made by applying a simplicia grinding machine to make herbal powder with the addition of crystal sugar. The results of the instant herbal formulations are then packaged and labeled. Instant herbal medicine business analysis training, assistance and marketing of instant herbal medicine products. After the Community Service program which was carried out with a training and mentoring approach to the Sawahan Village community and CV PJ ChingLung as a partner, they were able to increase the knowledge of the Sawahan Village community on how to make instant herbal medicine. There is product diversification in industrial partners as well as increased production capacity. Then the marketing reach that previously did not exist, now the marketing reach is expanded through exhibition networks and online sales. This community service activity is carried out under the right conditions because it is based on the needs of the community which are directly benefited.